Endovascular reconstruction of bilateral upper limbs ischemia in a patient with arterial outlet syndrome: A case report and literature review - Zhou, Mi; Jia, Wei; Jiang, Peng; Cheng, Zhiyuan; Zhang, Yunxin; Liu, Jianlong (Frontiers in Surgery, 2022)
Background：Acute upper limb ischemia in patient with thoracic outlet syndrome is a rare but serious clinical disorder. If the disease is not treated promptly due to underdiagnosis，that could lead to distal artery embolization and limb-threatening ischemia. Revascularization of upper extremity arteries in a timely manner could rescue ischemic limbs and improve patient' quality of life. We reported here a case of a patient presented with bilateral upper limb ischemia caused by arterial thoracic outlet syndrome. Case presentation：A 63-year woman presented with sudden bilateral upper extremities cold, numbness, pulseless and altered temperature sensation was firstly diagnosed with arterial thoracic outlet syndrome. The patient had performed a lot of pull-up and lat pull exercises in 2 months prior to the onset of the above symptoms. Color Doppler ultrasonography showed thrombosis in the right axillary artery, left subclavian and axillary artery. The patient received Rotarex mechanical thrombectomy combined with drug-coated balloon PTA to complete revascularization of the upper extremities and achieved a full recovery finally. Conclusions: Complete endovascular revascularization for the treatment of arterial thoracic outlet syndrome is a minimally invasive and effective method, especially for upper extremities ischemic lesions caused by non-bone compression.